Vietnam - Florence, Mason; Storey, Robert (Australia Lonely Planet, 2001)
Contents: facts about Vietnam; facts for the visitor; getting there and away; getting around; Hanoi; north-east Vietnam; north-west Vietnam; north-central Vietnam; central Vietnam; south-central coast; central highlands; Ho Chi Minh city; around Ho Chi Minh city; Mekong delta,...
Keywords: Quản trị DV Du lịch và Lữ hành